Digital Twin Technology for Real-Time Simulation and Optimization of Warehouses - Gautham Ram Rajendiran; Rajapriya Ayyadurai (North American Journal of Engineering Research, 2023)
The development of complex logistics environments, for example the growth of eCommerce sales and globalization of supplychains, revealed that traditional Warehouse management systems require a lot of operational overhead for carrying out the complexset of tasks. Digital Twin (DT) technology comes forward as the solution that facilitates real-time simulation, predictive analyticsand optimization of processes which has a great impact on the efficiency of operations. Through the generation of a virtual copyof physical warehousing facilities, those using DT technology can ensure that they have proper control and management of changesbetween the real and virtual environments since the decisions made in the real world have a way of reflecting on the virtual world.This paper aims to discuss the key concept of Digital Twin technology and its potential applicability in reducing complexity inWarehouse Management